Academic Performance of Pre-Clinical and Clinical Medical Students’ of East Coast Malaysian Peninsula: A Cross-Sectional and Descriptive Study That Stimulates Their Life - Rabiu Muazu Musa, Mainul Haque (Journal of Applied Pharmaceutical Science, 2017)
The education of medical students is held in high esteem in any nation due to the greater responsibility the profession is saddled with. Academic achievement of the students reflects their competency in their future profession. Although the knowledge, skill and desired attitude of the students improve as they gain experience, it is occasionally perceived that there is a dissimilarity in achievement because of diverse factors that impact on the academic performance of the students. The present study assesses various issues affecting the clinical and pre-clinical East Coast Malaysian medical students’ academic performance. A self-reported questionnaire which assesses various factors potentially affecting the academic performances of medical students was administered to a total of 232 students of both clinical and pre-clinical years, and Multivariate analysis of variance (MANOVA) was used in this study to analyze the data gathered. The study results found no significance difference in the GPA scores amongst gender and marital status across all the students, P>0.05. A statistically significant difference in GPA scores was found between the clinical and pre-clinical students P0.05. The results from the current study might be beneficial to the students by allowing them to comprehend better the factors that can affect their academic performance.
Keywords: Clinical Students, Pre-Clinical Students, Academic Performance, East Coast Malaysian Medical Students, Factors Affecting Academic Performance.